Comparing Island Effects for Different Dependency Types in Norwegian - Anastasia Kobzeva; Charlotte Sant; Parker T. Robbins; Myrte Vos; Terje Lohndal; Dave Kush (Languages, 2022)
Recent research suggests that island effects may vary as a function of dependency type, potentially challenging accounts that treat island effects as reflecting uniform constraints on all filler-gap dependency formation. Some authors argue that cross-dependency variation is more readily accounted for by discourse-functional constraints that take into account the discourse status of both the filler and the constituent containing the gap. We ran a judgment study that tested the acceptability of wh-extraction and relativization from nominal subjects, embedded questions (EQs), conditional adjuncts, and existential relative clauses (RCs) in Norwegian. The study had two goals: (i) to systematically investigate cross-dependency variation from various constituent types and (ii) to evaluate the results against the predictions of the Focus Background Conflict constraint (FBCC). Overall we find some evidence for cross-dependency differences across extraction environments. Most notably wh-extraction from EQs and conditional adjuncts yields small but statistically significant island effects, but relativization does not. The differential island effects are potentially consistent with the predictions of the FBCC, but we discuss challenges the FBCC faces in explaining finer-grained judgment patterns.